Hotspots and bottlenecks for the enhancement of the environmental sustainability of pig systems, with emphasis on European pig systems - Pexas, Georgios; Kyriazakis, Ilias (Springer, 2023)
Although pig systems start from a favourable baseline of environmental impact compared to other livestock systems, there is still scope to reduce their emissions and further mitigate associated impacts, especially in relation to nitrogen and phosphorous emissions. Key environmental impact hotspots of pig production systems are activities associated with feed production and manure management, as well as direct emissions (such as methane) from the animals and energy use. A major contributor to the environmental impacts associated with pig feed is the inclusion of soya in pig diets, especially since European pig systems rely heavily on soya imported from areas of the globe where crop production is associated with significant impacts of land use change, deforestation, carbon emissions, and loss of biodiversity. The “finishing” pig production stage contributes most to these environmental impacts, due to the amount of feed consumed, the efficiency with which feed is utilised, and the amount of manure produced during this stage. By definition therefore, any substantial improvements pig system environmental impact would arise from changes in feed production and manure management. In this paper, we consider potential solutions towards system environmental sustainability at these pig system components, as well as the bottlenecks that inhibit their effective implementation at the desired pace and magnitude. Examples include the quest for alternative protein sources to soya, the limits (perceived or real) to the genetic improvement of pigs, and the implementation of alternative manure management strategies, such as production of biogas through anaerobic digestion. The review identifies and discusses areas that future efforts can focus on, to further advance understanding around the potential sustainability benefits of modifications at various pig system components, and key sustainability trade-offs across the environment—economy—society pillars associated with synergistic and antagonistic effects when joint implementation of multiple solutions is considered. In this way, the review opens a discussion to facilitate the development of holistic decision support tools for pig farm management that account for interactions between the “feed * animal * manure” system components and trade-offs between sustainability priorities (e.g., environmental vs economic performance of pig system; welfare improvements vs environmental impacts).
Keywords: Pig production; Environmental impact; Sustainability; Trade-offs; Environmental impact hotspots; Implementation barriers; Climate change